2006
DOI: 10.1109/tap.2006.883983
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Standardized Model for Ultrawideband Propagation Channels

Abstract: Abstract-A comprehensive statistical model is described for ultrawideband (UWB) propagation channels that is valid for a frequency range from 3-10 GHz. It is based on measurements and simulations in the following environments: residential indoor, office indoor, builtup outdoor, industrial indoor, farm environments, and body area networks. The model is independent of the used antennas. It includes the frequency dependence of the path gain as well as several generalizations of the Saleh-Valenzuela model, like mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
493
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 640 publications
(512 citation statements)
references
References 41 publications
(49 reference statements)
12
493
0
7
Order By: Relevance
“…The distribution parameters for the dipole and double loop is gathered in Table 5. The suggested distributions differ from the ones usually seen in the literature, where S is often modeled as a lognormally [11,36] or a normally [14] distributed variable. …”
Section: Path-loss Modelsmentioning
confidence: 80%
See 1 more Smart Citation
“…The distribution parameters for the dipole and double loop is gathered in Table 5. The suggested distributions differ from the ones usually seen in the literature, where S is often modeled as a lognormally [11,36] or a normally [14] distributed variable. …”
Section: Path-loss Modelsmentioning
confidence: 80%
“…Perhaps the majority of the published papers are related to the various aspects of on-body situations [9][10][11][12]. For instance, in [7,[13][14][15] research related to UWB onbody radio channels are reported. In [7,12,[16][17][18][19], the effect of different antennas or polarizations on the UWB links are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the following, the values σ 0 = 0.01 m and β = 0.08 m are considered. These values are obtained in [15] by considering Channel Model 3 described in [16] and the energy detection receiver presented in [17], which is composed by a band-pass filter followed by a squarelaw device and an integrator, with integration interval set to T s = 1 s. The results presented in the following hold under these channel and receiver assumptions.…”
Section: Scenariomentioning
confidence: 99%
“…Furthermore, it was validated by Kolmogorov-Smirnov distribution-fitting to measurements at a significance level of 1% that the fading amplitudes can be modelled as Nakagami-m distributed [2].…”
mentioning
confidence: 99%
“…The corresponding wide sense stationary uncorrelated scattering (WSSUS) based channel impulse response (CIR) exhibiting clusters of similar delay paths may be modelled as [2]:…”
mentioning
confidence: 99%